Power dan Aktivisme Transnasional Dalam Studi Hubungan Internasional - Yusnarida Eka Nizmi (Universitas Nasional, 2018)
AbstractThis paper attempts to participate in the literature on the study of social movements and self-help groups operating across national borders. The purpose of this paper is to show a significant gap in the contextualisation of transnational activism between state and community organizations as well as NGOs. This paper will also try to give a new discourse on the issue of political activism in a transnational context. The process of globalization is not only purely economic and political elites. Cross-border interaction among civil society actors (globalization from below) is one of the phenomena in contemporary politics to receive high media and academic attention. When NGOs and social movements not only focus on domestic or local areas but also act across national borders, that is where transnational activity increases. Transnational political activity challenges conventional understanding of civil society and social movements as well as international relations.